Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Prove that $$x^n-y^n=(x-y)(x^{n-1}+x^{n-2}y+\ldots+xy^{n-2}+y^{n-1}).$$

This problem is driving me crazy.
$$x^n-y^n = (x-y)(x^{n-1}+x^{n-2}y+\dots +xy^{n-2}+y^{n-1)}$$

$(x^n-y^n)/(x-y) =$ the sum for the first $n$ numbers and then I added $(xy^{(n+1)-2}+y^{(n+1)-1})$ which should equal $(x^{n+1}-y^{n+1})/(x-y)$ but I can't figure it out


This is a similar problem in the book and I tried this method but it wasn't working out

$\quad$**Thereom $\bf1$-$\bf2$:** $\,\,\,\,$ If $\,x$ is any real number other than $1$, then $$\sum_{j=0}^{n-1}x^j=1+x+x^2+\ldots+x^{n-1}=\dfrac{x^n-1}{x-1}.$$ $\quad$**Remark:** $\displaystyle\sum_{j=0}^{n-1}A_j$ is shorthand for $A_0+A_1+A_2+\ldots+A_{n-1}.$
$\quad$**Proof:** Again we proceed by mathematical induction. If $n=1$ then $\displaystyle\sum_{j=0}^{1-1}x^j=x^0=1$ and $(x-1)/(x-1)=1$. Thus the theorem is true for $n=1$.
$\quad$ Assuming that $\displaystyle\sum_{j=0}^{k-1}x^j=(x^k-1)/(x-1)$, we find that $$ \eqalign{ \sum^{(k+1)-1}_ {j=0}x^j & = \sum^{k-1}_ {j=0}x^j+x^k=\dfrac{x^k-1}{x-1}+x^k \\ &= \dfrac{x^k-1+x^{k+1}-x^k}{x-1}\\ &= \dfrac{x^{k+1}-1}{x-1}. }$$ Hence condition $(\rm ii)$ is fulfilled, and we have established the theorem.

$\quad$**Corollary $\bf1$-$\bf1$:** $\,\,$ If $\,m$ and $n$ are positive integers and if $m>1$, then $n<m^n.$

share|improve this question
    
The second image is not a problem, but rather a theorem with a complete proof. Note that the first problem can be solved with this theorem by plugging in $\frac xy$ for §x§ and multiplying with $y^n$ (what care should be taken if $y=0$?) –  Hagen von Eitzen Jan 20 '13 at 22:14
add comment

4 Answers 4

up vote 7 down vote accepted

Hint: Apply $\textbf{Theorem 1.2}$ to $\displaystyle \frac{x}{y}$.

Edit: It follows from $\textbf{Theorem 1.2}$ that $\displaystyle \Bigl(\frac{x}{y}\Bigr)^n -1=\Bigl(\frac{x}{y}-1\Bigr)\Bigl( \Bigl(\frac{x}{y}\Bigr)^{n-1}+\cdots +\frac{x}{y}+1\Bigr)$.

Now multiply the equation by $y^n$ to get

$$\displaystyle y^n\Bigl(\Bigl(\frac{x}{y}\Bigr)^n -1)\Bigr)=y^n\Bigl(\frac{x}{y}-1\Bigr)\Bigl( \Bigl(\frac{x}{y}\Bigr)^{n-1}+\cdots +\frac{x}{y}+1\Bigr)$$

Simplifying on the left-hand side and rewritting $y^n$ as $yy^{n-1}$ on the right-hand side we get

$$(x^n -y^n)=yy^{n-1}\Bigl(\frac{x}{y}-1\Bigr)\Bigl( \Bigl(\frac{x}{y}\Bigr)^{n-1}+\cdots +\frac{x}{y}+1\Bigr)$$

Because the product is commutative you can rewrite the right-hand side to get

$$(x^n -y^n)=y\Bigl(\frac{x}{y}-1\Bigr)y^{n-1}\Bigl( \Bigl(\frac{x}{y}\Bigr)^{n-1}+\cdots +\frac{x}{y}+1\Bigr)$$

Finally, on the right-hand side, factor in $y$ and $y^{n-1}$ accordingly to get

$$(x^n -y^n)=(x-y)(x^{n-1}+\cdots +xy^{n-2}+y^{n-1})$$

share|improve this answer
    
So I tried expanding it if it were (x/y) –  draconisthe0ry Jan 20 '13 at 22:56
    
@draconisthe0ry was that a question somehow? –  Git Gud Jan 20 '13 at 23:23
    
Sorry about the last comment . . I didn't know that I ended up pressing the Add Comment button. I see that this works but what confuses me is that when you divide both sides by (x-y) and you get (x^(n−1)+x^(n−2)y+⋯+xy^(n−2)+y^(n−1)) It looks like "y" is following the theorem in the sense that it propagates as (y^0+y^1+...+y^(n-2)+y^(n-1)) and it is being multiplied that same sequence in reverse for x. I don't understand how the sequence in reverse for x is being multiplied in reverse order. –  draconisthe0ry Jan 22 '13 at 1:44
    
@draconisthe0ry I rewrote my answer with a more detailed explanation. Can you understand it now? –  Git Gud Jan 22 '13 at 7:24
    
yes this answer is perfect. i understand each step. the only concern I have is how to think of initially using (x/y) instead of x in Theorem 1-2. It makes sense on how that works since you can pull a y^n/y out of (x^n-y^n)/(x-y) to get ((x/y)^n-1)/(x/y-1) . Does this prove that the expression works for n+1 ? To prove it works for n+1 as well I would just show that ((x/y)^n-1)/(x/y-1) + (x/y)^n = ((x/y)^(n+1)-1)/((x/y)-1) right ? –  draconisthe0ry Jan 22 '13 at 17:43
show 2 more comments

Your induction hypothesis is that

$$\sum_{j=0}^{k-1}x^jy^{(k-1)-j}=\frac{x^k-y^k}{x-y}\;.$$

Now follow the model:

$$\begin{align*} \sum_{j=0}^{(k+1)-1}x^jy^{k-j}&\overset{(1)}=\left(\sum_{j=0}^{k-1}x^jy^{k-j}\right)+x^ky^0\\ &\overset{(2)}=y\left(\sum_{j=0}^{k-1}x^jy^{(k-1)-j}\right)+x^k\\ &\overset{(3)}=y\cdot\frac{x^k-y^k}{x-y}+x^k\\ &\overset{(4)}=\frac{x^ky-y^{k+1}+x^{k+1}-x^ky}{x-y}\\ &\overset{(5)}=\frac{x^{k+1}-y^{k+1}}{x-y}\;. \end{align*}$$

$(1)$ is splitting off the last term of the summation; $(2)$ factors a $y$ out of the remaining summation; $(3)$ uses the induction hypothesis; and $(4)$ and $(5)$ are just algebra.

share|improve this answer
    
I'm trying to make sense of it now . . . So I see that (1 + y^1 + ... + y^(n-1)) = (y^n-1)/(y-1) but it is being multiplied by (x^(n-1)+...+x^1+1) so that is equal to (x^n-1)/(x-1) but would that work when you multiply them ? –  draconisthe0ry Jan 20 '13 at 22:47
    
@draconisthe0ry: I’m not sure what you’re asking. I’m simply observing that $$x^n-y^n = (x-y)(x^{n-1}+x^{n-2}y+\dots+xy^{n-2}+y^{n-1)}\;,$$ the statement that you want to prove, is equivalent to $$\sum_{k=0}^{n-1}x^ky^{(n-1)-k}=\frac{x^n-y^n}{x-y}$$ and then proving the latter by induction. (Actually, they’re not equivalent when $x=y$, but in that case the first one is trivially true, since both sides are $0$.) This is exactly what your text did with the $x^n-1$ identity: it converted $x^n-1=(x-1)(\text{stuff})$ to $\text{stuff}=\frac{x^n-1}{x-1}$ and proved that. –  Brian M. Scott Jan 20 '13 at 22:56
add comment

$$\frac{1-(x/y)^n}{1-x/y}=1+x/y+(x/y)^2+...+(x/y)^{n-1}$$ $$\frac{(y^n-x^n)/y^n}{(y-x)/y}=\frac{y^{n-1}+xy^{n-2}+...+x^{n-1}}{y^{n-1}}$$ $$\frac{y^n-x^n}{(y-x)y^{n-1}}=\frac{y^{n-1}+xy^{n-2}+...+x^{n-1}}{y^{n-1}}$$ $$y^n-x^n=(y-x)(y^{n-1}+xy^{n-2}+...+x^{n-1})$$

share|improve this answer
    
Effective answer. +1 –  B. S. Jan 21 '13 at 10:32
    
Ok so I see how you switched x and y . . . I also see how you can pull out y^n from the numerator and y from the denominator to get ((x/y)^n-1)/((x/y)-1) . what i don't understand is when you multiply the top and bottom of the RHS by y^(n-1) you get y^(n-1)+y^(n-2)+...+y^0 ? I get why the first two are y^(n-1) and y^(n-2) but as the sequence progresses wouldn't it keep going to y^(n-infinity) . i feel like that is a dumb question but i'm not getting it and that's the one part that is stopping me from finishing the problem –  draconisthe0ry Jan 22 '13 at 4:10
add comment

Let $u_n$ $=$ $x^n-y^n$. Now note that $u_n$ $=$ $(x+y)u_n$$_-$$_1$ $+$ $xy$ $u_n$$_-$$_2$. Assume that the given expression is true for all numbers from $1$ to some fixed $k(>1)$. Then apply induction to prove the result for $(k+1)$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.